Photovoice as a Participatory Extension Approaches Method in Expressing Youth Views of Agricultural Work - Husnul Hidayah; Sarwititi Sarwoprasodjo; Krishnarini Matindas (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2020)
This study aims to: 1) reveal the views of youth regarding agricultural issues through photovoice and 2) evaluate photovoice as a Participatory Extension Approaches (PEA) method. This study uses the photovoice method. The premise of photovoice is to empower people through documentary photography. Photovoice is a method of placing cameras in the hands of people whose voices are often silenced by the power elite. The subjects of this study were grouped into two, namely main informants and supporting informants. Data collection techniques were carried out by in-depth interviews and focus group discussions. The results showed that photovoice is a method that empowers youth by increasing the ability of youth to express their views, thoughts, concerns and hopes regarding agricultural issues which are described through agricultural potential, farming problems and agricultural work. The application of the Participatory Extension Approaches method through the photovoice method is the most appropriate method in the community empowerment process, because in the process of making it aware of the problems and potentials that exist in people's lives, which not only makes the community the object of change, but also as the agent of change.